Capital Intelektual, Efisiensi Modal, Kebijakan Deviden, dan Nilai Perusahaan - Ardiansyah, Eka (E-Jurnal Akuntansi; Vol 31 No 6 (2021)DO - 10.24843/EJA.2021.v31.i06.p05, 2021)
Stakeholders have a tendency to judge the company in making policies. So that in the company appraisal process, it requires consideration of the various factors that shape the value of the company itself. Therefore, the purpose of this study is to see how much influence intellectual capital, capital efficiency and dividend policy have on the value of companies that have published their financial reports on the Indonesia Stock Exchange (IDX). The total population used was 90 companies and the samples taken were 25 companies in the financial sector. The sampling method uses purposive sampling which aims to ensure that the sample taken can meet the required criteria. Data analysis using PLS (Partial Least Square) in order to be able to analyze many variables at once, data analysis with PLS is assisted by the Smart PLS application. From the research results, it is found that intellectual capital has a positive effect on firm value, while the effect of dividend policy and capital efficiency on firm value has a negative effect . Keywords: Intelectual Capital; Devidend Policy; Capital Efficiency; Corporate Value.